The Factor of Main Characters’ Consumer Behavior in Toy Story and Toy Story 2 - Louis Adhitama (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This thesis aims to know why the main characters of Toy Story and Toy Story 2 do excessive consumption on toys. Therefore, I will use the theory of consumer behavior to be applied on Andy, Sid, and Al as the consumers of toys. From this theory, I want to show that consumer behavior can be seen from internal and external traits. The internal trait means the consumer behavior is influenced by the inner side of consumers. On the other hand, the external trait means the consumer behavior is triggered by the outside factor of consumers’ surroundings. I connected the analysis with consumer behavior theory by discussing the factors which have internal and external traits that cause the main characters to have consumer behavior.  In the end, it can be concluded from Toy Story (1995), and Toy Story 2 (1999) that consumer behavior can influence children or adult for doing excessive consumption as the consumers of toys. Keywords: Affective System, Cognitive System, Characteristic, Consumer Behavior, Consumption.